Controls, procedures and risk - Loader, David (Securities Institute Operations Management S.)
Controls, Procedures and Risk' covers the skills and procedures needed to enable the monitoring and managing of risk and the authors focus on procedures design, implementation and documentation. Considerable emphasis is also given to the key controls and the importance of control functions, audit and risk management groups and policy. Case studies are used to effectively demonstrate 'success' and 'failure'. In the financial services industry risk is a constant threat to organizations of all sizes and to the markets themselves. Many industry 'events' have shown how dangerous it is when a busine.